Innovation of Basic Education Curriculum to Optimize Learners Spiritual Character - Santy Afriana; Mohamad Agung Rokhimawan (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2022)
The innovation of the Islamic basic education curriculum needs to link learning materials with spiritual character values ​​to become a reference for students in their daily behavior. This study aims to determine the innovation of the Islamic basic education curriculum in optimizing the spiritual character of students. This research uses the library research literature, which stands under the review method, which is descriptive-analytical. The data analysis technique used is the content analysis method to obtain valid references and can be re-examined based on the context. Islamic basic education is an effort to instill spiritual character values ​​ to make whole students beings intellectually, emotionally, and spiritually. The innovation of the Islamic basic education curriculum in optimizing the spiritual character requires educators' readiness to design learning by preparing various materials and learning media that can concretely package material. Further researchers are expected to be able to contribute to curriculum innovation in other aspects of character and to be able to use field research so that the results of the data are more empirical.